Field Research on Global Climate Change in Social Reality - Fatma Karakuş Kaçmaz (Sosyal Siyaset Konferansları Dergisi)
This study focuses on revealing the relationship between global climate change (GCC) and the discipline of social policy on the axis of social reality. The focus of the study is qualitative research carried out within the framework of nature-based work (those who make their living from nature) in the Mediterranean climate of Turkey to make the dimensions of the GCC in social reality comprehensible. Within the scope of the study, in-depth interviews were conducted with those who have been making a living directly from nature for long enough to assess climatic changes. In line with the Interpretive Approach adopted in the research, the Constructivist Design Theory was preferred to understand the interaction between the GCC and human beings within the scope of social policy, in the ordinary course of life and in-depth. The findings show that GCC increases production costs in works directly dependent on nature. Due to the increases in production costs, GCC threatens the potential of works directly dependent on nature as a livelihood. On the one hand, this impoverishes those who work directly depending on nature. On the other hand, it interrupts the handover of this work to future generations. According to this research, which aims to explore the relationship between the phenomenon of GCC and the discipline of social policy, the impoverishing cycle caused by GCC makes it necessary for GCC to be a ‘new’ topic in the field of social policy. This cycle also makes effective social policy practices necessary in dealing with GCC.